Neurovascular Imaging with Ultra-High-Resolution Photon-Counting CT: Preliminary Findings on Image-Quality Evaluation - Tóth, Adrienn; Chetta, Justin A.; Yazdani, Milad; Matheus, M. Gisele; O‘Doherty, Jim; Tipnis, Sameer V.; Spampinato, M. Vittoria (American Journal of Neuroradiology, 2024)
BACKGROUND AND PURPOSE: The first-generation photon-counting detector CT was recently introduced into clinical practice and represents a promising innovation in high-resolution CT imaging. The purpose of this study was to assess the image quality of ultra-high-resolution photon-counting detector CT compared with energy-integrating detector CT and to explore different reconstruction kernel sharpness levels for the evaluation of intracranial aneurysms.MATERIALS AND METHODS: Ten patients with intracranial saccular aneurysms who had previously undergone conventional energy-integrating detector CT were prospectively enrolled. CT angiograms were acquired on a clinical dual-source photon-counting detector CT in ultra-high-resolution mode and reconstructed with 4 vascular kernels (Bv36, Bv40, Bv44, Bv48). Quantitative and qualitative image-quality parameters of the intracranial arteries were evaluated. For the quantitative analysis (image noise, SNR, contrast-to-noise ratio), ROIs were manually placed at standard anatomic intracranial and extracranial locations by 1 author. In addition, vessel border sharpness was evaluated quantitatively. For the qualitative analysis, 3 blinded neuroradiologists rated photon-counting detector CT and energy-integrating detector CT image quality for the evaluation of the intracranial vessels (ie, the aneurysms and 9 standard vascular branching locations) on a 5-point Likert-type scale. Additionally, readers independently selected their preferred kernel among the 4 kernels evaluated on photon-counting detector CT.RESULTS: In terms of quantitative image quality, Bv48, the sharpest kernel, yielded increased image noise and decreased SNR and contrast-to-noise ratio parameters compared with Bv36, the smoothest kernel. Compared with energy-integrating detector CT, the Bv48 kernel offered better quantitative image quality for the evaluation of small intracranial vessels (P < .001). Image-quality ratings of the Bv48 were superior to those of the energy-integrating detector CT and not significantly different from ratings of the B44 reconstruction kernel. When comparing side by side all 4 photon-counting detector reconstruction kernels, readers selected the B48 kernel as the best to visualize the aneurysms in 80% of cases.CONCLUSIONS: Ultra-high-resolution photon-counting detector CT provides improved image quality for neurovascular imaging. Although the less sharp kernels provided superior SNR and contrast-to-noise ratio, the sharpest kernels delivered the best subjective image quality on photon-counting detector CT for the evaluation of intracranial aneurysms.AcomAanterior communicating arteryBvbody vascularCNRcontrast-to-noise ratioCTDIvolCT dose index volumeEIDenergy-integrating detectorOAophthalmic arteriesPCDphoton-counting detectorPcomAposterior communicating arteryQIRquantum iterative reconstructionSOCstandard of careUHRultra-high-resolutionVBvertebral artery–basilar artery junctions